An overview on different aspects of hypodermosis: Current status and future prospects - Ahmed, Haroon; Afzal, Muhammad Sohail; Mobeen, Muhammad; Simsek, Sami (Elsevier, 2016)
Livestock plays a vital role in economic development of a nation and is being used in agriculture for draft power, production of farmyard manure as well as milk and meat production. Bovine hypodermosis is the top culprit among all parasitic infections across the world. Hypodermosis is an endemic disease in the mountainous areas/plain areas and is regularly observed in the northern hemisphere of the globe affecting cattle, deer, yaks and buffaloes. There is a wide variation in geographical distribution of Hypoderma spp. during the years 1945-2015. The manuscript includes a geospatial study that tries to maps the global distribution of hypodermosis in different areas of the world in order to detect hotspots or endemic areas that may be a potential source for disease spread. This information's are very useful to predict the potential high risk areas that are prone to disease outbreak. The present review aims to evaluate the global distribution, molecular discrimination, diagnostics and vaccination of hypodermosis, focusing on its current status and future perspectives towards the management of the disease and its control strategies. (C) 2016 Elsevier B.V. All rights reserved.
Keywords: Hypodermosis; Distribution; Molecular diagnostics; Vaccination; Recommendations